Using data insertion with the NAME model to simulate the 8 May 2010 Eyjafjallajökull volcanic ash cloud. Issue 1 (7th January 2016) - Wilkins, K. L.; Watson, I. M.; Kristiansen, N. I.; Webster, H. N.; Thomson, D. J.; Dacre, H. F.; Prata, A. J.
Abstract: A data insertion method, where a dispersion model is initialized from ash properties derived from a series of satellite observations, is used to model the 8 May 2010 Eyjafjallajökull volcanic ash cloud which extended from Iceland to northern Spain. We also briefly discuss the application of this method to the April 2010 phase of the Eyjafjallajökull eruption and the May 2011 Grímsvötn eruption. An advantage of this method is that very little knowledge about the eruption itself is required because some of the usual eruption source parameters are not used. The method may therefore be useful for remote volcanoes where good satellite observations of the erupted material are available, but little is known about the properties of the actual eruption. It does, however, have a number of limitations related to the quality and availability of the observations. We demonstrate that, using certain configurations, the data insertion method is able to capture the structure of a thin filament of ash extending over northern Spain that is not fully captured by other modeling methods. It also verifies well against the satellite observations according to the quantitative object‐based quality metric, SAL—structure, amplitude, location, and the spatial coverage metric, Figure of Merit in Space. Key Points: Eyjafjallajökull ash cloud is simulated using data insertion Captures regional‐scale ash cloud structure Results evaluated using spatial metrics